(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
A cross sectional study was carried out from July 2004 to June 2006 at the department of ENT of SSMC and Mitford Hospital, Dhaka with the aim to assess the graft take rate as well as hearing improvement. This study included 60 patients those underwent myringoplasty operations by underlay technique with temporalis fascia graft. The age range of patients was 15-45 years. In this study graft take rate was 86.67% after 2 months. There was no gross difference in graft take in respect of sex. The pre operative and post operative hearing threshold is statistically significant which indicates improvement of hearing. Therefore, myringoplasty is a valid treatment modality for closing perforation of tympanic membrane, prevention of infection and improvement of hearing. Bangladesh J Otorhinolaryngol; April 2018; 24(1): 62-67